2015
DOI: 10.4273/ijvss.7.3.07
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Electrical Actuator and Air Spring Actuator Controlled Suspension Systems for Automotive Vehicles

Abstract: This article discusses methods to reduce the acceleration of a vehicle and increase its road holding ability. In the simulation using quarter car model, electric actuator and air spring based actuator are used as the main control elements. A three degrees of freedom system model is used in which the parameters for the tire, vehicle body and seat are considered. The required actuator force is calculated by a standard fuzzy controller. For analysing the performance of active suspension system, body acceleration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Simulation results showed that the proposed control strategy can effectively adjust parameters based on changing road conditions. Sathishkumar [7] used a fuzzy control strategy to actively control the three-degrees-of-freedom air suspension seat model of the 1/4 vehicle. The vehicle body acceleration and velocity were used as inputs to the controller, and the acceleration of the seat and the output of the vehicle body were analyzed to evaluate the performance of the active suspension system.…”
Section: Introductionmentioning
confidence: 99%
“…Simulation results showed that the proposed control strategy can effectively adjust parameters based on changing road conditions. Sathishkumar [7] used a fuzzy control strategy to actively control the three-degrees-of-freedom air suspension seat model of the 1/4 vehicle. The vehicle body acceleration and velocity were used as inputs to the controller, and the acceleration of the seat and the output of the vehicle body were analyzed to evaluate the performance of the active suspension system.…”
Section: Introductionmentioning
confidence: 99%
“…25 Sathishkumar used a fuzzy control strategy to actively control the 3-DOF air suspension system model of 1/4 vehicle. 26 In order to analyze the performance of the active suspension system, the seat and body acceleration were selected to judge the state of the control system. At the same time, the semi-active air suspension system of light vehicle was analyzed by fuzzy and PID control strategies.…”
Section: Introductionmentioning
confidence: 99%